Degradation kinetics of stabilized Pluronic micelles under the action of ultrasound - Husseini, Ghaleb (2009)
The majority of research in the area of acoustically-activated drug delivery from stabilized micelles has been focused on the rapid release of chemotherapy drugs from the core of such nano-carriers. Previous publications have shown that low-frequency ultrasound is able to release approximately 2% of Doxorubicin (Dox) from the core of Pluronic P105 micelles stabilized using a cross-linked network of N,N-diethylacrylamide (NanoDeliv™) within 2 s of applying 70-kHz ultrasound. Here we use a custom-made ultrasound exposure chamber with fluorescence detection to measure the long-term fluorescence emissions of Dox from the NanoDeliv™ after 2 h of exposure to two ultrasound frequencies, 70 and 476 kHz, at a mechanical index of 0.9. Fluorescence measurements are then used to deduce the degradation kinetics of stabilized Pluronic micelles during 24 h following exposure to ultrasound. Results show that ultrasound does disrupt the covalent network of the stabilized micelles, but the time constant of network degradation is very long compared to the time constant pertaining to drug release from micelles. Experiments also show no significant difference in degradation rates when employing the two frequencies in question at the same mechanical index.